Analysis of the quality of tourist services in the Fortress of São José da Ponta Grossa - Florianópolis, using TOURQUAL - Mondo, Tiago Savi; Soares, Maria Helena Alemany; Leite, Fabiana Calçada de Lamare; Tonera, Roberto (Revista Turismo em Análise, 2020)
Heritage tourism has consolidated itself as a prominent segment in the scope of tourism products. Making the attraction competitive becomes a challenge for its managers and the offer of a quality tourist service helps in the construction of positive value and image and consequent business development. The objective of this research is to analyze the perception of tourists regarding the quality of tourist services offered at the Fortaleza de São José da Ponta Grossa in Florianópolis - SC. For this, an applied, quantitative, field research was carried out. The instrument was the closed questionnaire based on the Tourqual model. The data were collected from May to November 2019. The sample consisted of 398 tourists, considered non-probabilistic for convenience. The data were analyzed using descriptive statistics, normality test, multiple linear regression and Spearman correlation in SPSS 22. The main results indicate a level of satisfaction of 9.55 (maximum 10) and an average of the quality indicators of 8,48. The best indicators for tourists were: Beauty at the Attraction, Escape from the Tourist Routine / New experiences and Visitor Guide Service. While the worst assessed were Accessibility, Technology and Accessible Bathrooms. When applying the multiple linear regression model, it was found that 96.1% of the variance of quality indicators explains the variance of the tourist satisfaction construct, demonstrating that quality is really a causal antecedent of satisfaction and that the management of indicators leads to development attractive as a tourist product.